Sermones selecti - Augustinus, Aurelius, Heiliger 354-430 (Corpus scriptorum ecclesiasticorum Latinorum, 2015)
Modern scholars have neglected some of the sermons of Augustine of Hippo (354-430 AD) because they considered them inauthentic. This volume argues in favor of the authenticity of more than ten of these sermons, and for the first time, presents them in a critical edition. In addition, several sermons previously known to be authentic are presented for the first time in a complete version. Clemens Weidmann, Universität Salzburg, Österreich.